Excellent Medium-Temperature Thermoelectric Performance of Monolayer BiOCl - Gan, Yan (Langmuir : the ACS journal of surfaces and colloids, 2022)
Recently, a ternary-layered material BiOCl has elicited intense interest in photocatalysis, environmental remediation, and ultraviolet light detection because of its unique band gap of around 3.6 eV, low toxicity, and earth abundance. In particular, Gibson et al. reported a measurement of the in-plane thermal conductivity of BiOCl experimentally using a four-point-probe method [Science, 373, 1017-1022 (2021)], which is only 1.25 W/m K at 300 K. Motivated by the work, we studied the thermoelectric property of monolayer BiOCl using first-principles calculations combined with the Boltzmann transport equation. The calculated phonon thermal conductivity of monolayer BiOCl is 3 W/m K at 300 K, which is far below that of other promising 2D thermoelectric materials like graphyne and MoS2. A comprehensive analysis of phonon modes is conducted to reveal the low thermal conductivity. Moreover, the maximal ZT value is as high as 1.8 at 300 K and 5.7 at 800 K for the p-type doping with the 2 × 1015 cm-2 concentration. More importantly, we found that the thermoelectric efficiency of such 2D materials is significantly enhanced to 8 at 800 K by applying 1.5% tensile strain, which clearly outperforms that of the reported 2D thermoelectric material SnSe. The results shed light on the promising application in medium-temperature (600-900 K) thermoelectric devices